SIMULATION IN SEXUAL HEALTH: USING SIMULATION TO TEACH JUNIOR DOCTORS TECHNICAL AND NON- TECHNICAL SKILLS IN GENITO-URINARY MEDICINE. (13th May 2015) - Omer, Rasha; Campbell, Lesley; Swaris, Samanthi; Schatzberger, Rebecca; Loftus, Hannah; Briggs, Aparna; Dilke-Wing, Gillian
Abstract : Background: In the UK, Clinical simulation is strongly recommended for training in Medicine. In Genito-urinary Medicine, simulation is used for summative assessment for major examination such as Dip GUM and Dip HIV. Unfortunately it's rarely used for training. New Trainees in GUM have very little experience in Sexual Health. A recent in-house survey showed around 85% would have found simulation useful if included in the induction program and would have addressed training needs specific to the speciality. Methodology: All new trainees will be invited to participate. Faculty will consist of GUM Consultants and Registrars. The course will consist of 2 parts Skills Workshop Using part-task trainers, candidates will rotate through 5 Stations that will include: -Female Pelvis: for speculum insertion, cervical cytology, Microbiology sampling and bimanual examination -Male Pelvis: for examination and sampling techniques -Rectal examination: for proctoscopy and prostate examination -Anatomy of Male and female genital tract using illustrations -Illustrations of Common Dermatological conditions and skin infections and cryotherapy for warts. Scenario-based Simulation: Trainees will participate in simulated communication scenarios. Objectives:  1. To demonstrate good listening skills 2. To use simple, clear language when communication with patients 3. To develop understanding of ethics, law and consent. Results: We anticipate that trainees will have more confidence during clinical consultations and in managing challenging cases. Conclusions: Better understanding of the team dynamics and nature of work in GUM will improve working relationships which will ultimately result in better patient care.